Beyond the Legacy of the Missionaries and East Indians : the Impact of the Presbyterian Church in the Caribbean - Teelucksingh, Jerome (Caribbean Series., 2019)
In Beyond the Legacy of the Missionaries and East Indians, Jerome Teelucksingh offers a revisionist perspective of the role of the Presbyterian Church in Trinidad. He is particularly interested in the enlightenment of the society, especially the faster rate of social mobility achieved by the Indo-Caribbean diaspora in the era following the First World War. He argues that the Presbyterian Church in the Caribbean was particularly interested in women's rights b yproviding the vital human and financial resources needed to champion the elevation of Indian women. By simultaneously providing a formal education whilst assisting the poor and oppressed, the Canadian missionaries and locally-trained persons played a pivotal role in the colonial society. He closely examines the dynamic between local expertise and Canadian missionary work in such social uplift processes.--